1990
DOI: 10.1007/bf02018315
|View full text |Cite
|
Sign up to set email alerts
|

Retardation of coronary artery disease in humans by the calcium-channel blocker nifedipine: Results of the INTACT study (International Nifedipine Trial on Antiatherosclerotic Therapy)

Abstract: Experimental studies have demonstrated a 30-50% reduction in the development of atheromatous lesions of the aorta in rabbits fed a diet rich in cholesterol when they were treated with nifedipine. Based on these favorable results, we designed a multicenter, placebo (PL)-controlled, randomized, double-blind study, to test the effect of 80 mg nifedipine (NIF) per day versus placebo on the progression of mild coronary artery disease (CAD) (further development of existing stenoses, especially formation of new steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…12,13 As NO has important antiatherogenic properties, 47 whereas endothelial dysfunction and production of oxidative stress, which are characteristic not only of hypertension but also of the most important cardiovascular risk factors, 44 are associated with cardiovascular events, [17][18][19] it is conceivable that the possibility of restoring NO availability could represent an additional effect of calcium entry blockers, one that would help to prevent the development of atherosclerosis and possibly of clinical events. In line with this interpretation, several clinical studies demonstrate that a calcium antagonist-based treatment can reduce the progression of new atherosclerotic coronary 48 or carotid lesions. 49 However, the suggestion that restoration of endothelial function by calcium antagonists or by other drug classes active on endothelium-dependent vasodilation could contribute to reduction of cardiovascular events, not only in hypertensive patients but also in subjects with cardiovascular disease, is at the present time only an attractive hypothesis that needs to be demonstrated by specific clinical trials.…”
Section: Perspectivesmentioning
confidence: 76%
“…12,13 As NO has important antiatherogenic properties, 47 whereas endothelial dysfunction and production of oxidative stress, which are characteristic not only of hypertension but also of the most important cardiovascular risk factors, 44 are associated with cardiovascular events, [17][18][19] it is conceivable that the possibility of restoring NO availability could represent an additional effect of calcium entry blockers, one that would help to prevent the development of atherosclerosis and possibly of clinical events. In line with this interpretation, several clinical studies demonstrate that a calcium antagonist-based treatment can reduce the progression of new atherosclerotic coronary 48 or carotid lesions. 49 However, the suggestion that restoration of endothelial function by calcium antagonists or by other drug classes active on endothelium-dependent vasodilation could contribute to reduction of cardiovascular events, not only in hypertensive patients but also in subjects with cardiovascular disease, is at the present time only an attractive hypothesis that needs to be demonstrated by specific clinical trials.…”
Section: Perspectivesmentioning
confidence: 76%
“…When all 348 patients with and without protocol violations who underwent two study angiograms, were considered in the analysis of data, again no significant differences were found between the two study groups with regard to changes in preexisting lesions [35]. The significant difference between the two treatment groups in the number of new lesions per patient, however, was confirmed by this 'in- For definitions see Table 4; stenoses changing to occlusions are excluded.…”
Section: Resultsmentioning
confidence: 77%
“…In either treatment group, angina pectoris symptoms were slightly reduced during the study. For further informations on protocol violations and clinical follow-up see references [31,[34][35][36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After analysing these studies, it is clear that the CCBs controversies have not been elucidated yet. 35,36 For example, the INTACT study 31,37,38 showed a reduced atherosclerotic plaque progression in the nifedipine group than in the control group (angiographically). Nevertheless, cardiovascular mortality was larger in the nifedipine group.…”
Section: Human Investigations Trials Failures and The Futurementioning
confidence: 99%